PENGETAHUAN IBU HAMIL TENTANG PENTINGNYA INISIASI MENYUSUI DINI PADA BAYI BARU LAHIR (LITERATUR REVIEW) - Suhartini; Yudiarsi Eppang (Stikes Graha Edukasi Makassar, 2022)
Early initiation of breastfeeding (IMD) is the first step in the success of exclusive breastfeeding. Colostrum contained in breast milk is useful for increasing the baby's immune system and reducing the IMR due to hypothermia. In addition, IMD is also useful for the relationship between mother and baby and makes babies feel calm. Early initiation of breastfeeding is the proportion of children born in the last 24 months who were placed at the breast within one hour of birth. According to Riskesdas 2018, nationally the IMD coverage is 58.2%, this figure needs to be increased to achieve the global target of 70%. There are factors that influence the practice of IMD, namely the attitude of the mother, the role of health workers, and the support of the closest people. The aim is to determine the knowledge of pregnant women about the importance of early initiation of breastfeeding in newborns. Method The research method used in this study is a literature review with the search for sources used, namely Google Scholar and indexed by Scopus with six literature publications from 2017-2021. Result: there is a relationship between mother's knowledge on the importance of early breastfeeding initiation in newborns. Conclusion: Based on the analysis that has been carried out that mother's knowledge about early initiation of breastfeeding will provide benefits for the baby and mother where imd will increase the bond of love between mother and baby and baby and mother feel calmer